2018
DOI: 10.26504/qec2018aut_sa_otoole
|View full text |Cite
|
Sign up to set email alerts
|

Exploring SME investment patterns in Ireland: New survey evidence

Abstract: An empirical profile of SME investment in Ireland is critical to understanding the growth possibilities and productive capacity of Irish indigenous enterprises. However little is known about SME investment activity outside the more aggregate information. This paper uses new survey evidence compiled as part of the Department of Finance SME Credit Demand Survey to profile the types of assets SMEs are investing in, how firms are financing these investments and what barriers firms face to investment. We provide a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…1 As the Irish economy recovered rapidly from the financial crisis, a clear feature of the SME market was a slow recovery in capital investment and an apparent low appetite for external borrowing. This is evident from previous research which has indicated sustained increases in firm turnover and profitability but a continued low share of external finance usage with internal funding of investment dominating (Gargan et al, 2018;Lawless et al, 2020b). This context in the period just prior to the onset of the pandemic led to questions being raised around whether demand-side factors (such as uncertainty or risk appetite) were outweighing supply-side investment determinants (such as the cost of, and access to, financing).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…1 As the Irish economy recovered rapidly from the financial crisis, a clear feature of the SME market was a slow recovery in capital investment and an apparent low appetite for external borrowing. This is evident from previous research which has indicated sustained increases in firm turnover and profitability but a continued low share of external finance usage with internal funding of investment dominating (Gargan et al, 2018;Lawless et al, 2020b). This context in the period just prior to the onset of the pandemic led to questions being raised around whether demand-side factors (such as uncertainty or risk appetite) were outweighing supply-side investment determinants (such as the cost of, and access to, financing).…”
Section: Introductionmentioning
confidence: 85%
“…This change also highlighted a marked increase in the share of firms self financing activities, a feature which has continued to date. More recent research has indicated a rebound in investment such as Gargan et al (2018) and Lawless et al (2020b). However, investment is still lower than would be expected with such a fast growing economy.…”
Section: Performance Of Smes In Irelandmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary data source we used for the analysis of SMEs in this paper is the Credit Demand Survey (CDS), carried out twice a year by the Department of Finance. The survey is documented in detail in Gargan et al (2018) and Martinez-Cillero et al (forthcoming). It contains a wide range of financial and credit indicators, which we briefly overview here.…”
Section: Financial Position Of Smes Prior To the Pandemicmentioning
confidence: 99%
“…The first results of this survey were presented in Gargan et al (2018). The aim of this report is to provide an annual statistical update on the indicators presented in this article and to review trends in investment across SMEs over time.…”
Section: Introductionmentioning
confidence: 99%